Law Enforcement in the Context of Legal Culture in Society - Derita Prapti Rahayu; Faisal Faisal; Rafiqa Sari; Ndaru Satrio (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2020)
Law enforcement is a series of processes to describe values, ideas, ideals, and subsequently become legal objectives. The awareness and compliance of sailing administration to Matras fishermen in catching fish is very much determined by the legal culture of the community. The purpose of this discussion is to determine law enforcement in the context of legal culture in society. The results of the discussion conclude that the legal culture of Matras fishermen displays something unique, namely a spiritual presence and a contextual existence. Therefore, law enforcement in the cultural context is sharing space with the other side of the value that is believed to be sacred in religious substance and believing in the value of local wisdom. The pattern of law enforcement with a cultural dimension is a manifestation of synchronization of the various aspects of substance, structure and culture itself